(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article deals with the aesthetic and moral category as the main factors of the internal world of the student in the context of literary and noosphere education. Posted methodological development training session for the study of Galina Malik Fairy Story " The Extraordinary Adventures of Ali in the country Nedoladiyi " The material focuses on the relevance of the issue of disclosure of the spiritual potential of the individual .